Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/pl00013792
|View full text |Cite
|
Sign up to set email alerts
|

The influences of muscle fibre proportions and areas upon EMG during maximal dynamic knee extensions

Abstract: This study is an investigation of the relationship between muscle morphology and surface electromyographic (EMG) parameters [mean frequency of the power spectrum (MNF), signal amplitude (root mean square, RMS) and the signal amplitude ratio (SAR; i.e. the ratio between the RMS level during the passive part of the contraction cycle and the RMS level during the active part of the contraction cycle)] during 100 maximal dynamic knee extensions at 90 degrees. s(-1). Each contraction cycle comprised of 1 s of active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
5
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 39 publications
(50 reference statements)
4
80
5
2
Order By: Relevance
“…By contrast, the electrical properties of the sarcolemma have been shown to vary between fast and slow fibre types within mammals (Luff and Atwood, 1972). As these properties will determine the conduction velocity of an action potential (Buchtal et al, 1955), it can be predicted that faster motor units will have faster conduction velocities and hence generate higher myoelectric frequencies (Gerdle et al, 2000;. We therefore interpret that a higher value of , representing relatively more low frequency signal content, can be associated with the recruitment of slower motor units.…”
Section: Discussionmentioning
confidence: 86%
“…By contrast, the electrical properties of the sarcolemma have been shown to vary between fast and slow fibre types within mammals (Luff and Atwood, 1972). As these properties will determine the conduction velocity of an action potential (Buchtal et al, 1955), it can be predicted that faster motor units will have faster conduction velocities and hence generate higher myoelectric frequencies (Gerdle et al, 2000;. We therefore interpret that a higher value of , representing relatively more low frequency signal content, can be associated with the recruitment of slower motor units.…”
Section: Discussionmentioning
confidence: 86%
“…This evidence is based, in large part, on analyzing the time-varying frequency spectra of electromyographic (EMG) signals (see reviews by Hodson-Tole and Wakeling, 2009;Raez et al, 2006). Different motor unit types have muscle fibers with different electrical membrane properties (Luff and Atwood, 1972), and there is an intrinsic speed dependence of the EMG frequency such that faster fibers generate higher-frequency signals (Gerdle et al, 2000;Hodson-Tole and Wakeling, 2008b;Lee et al, 2011). For example, when human subjects cycle at increased cadences, EMG signals from the gastrocnemii shift to higher frequencies (Wakeling et al, 2006), consistent with the recruitment of faster motor units (Citterio and Agostoni, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The same authors [15] also concluded that the EMG power spectrum might contain information about the features of muscle fibres. These suggestions were confirmed by Gerdle, Karlsson, Crenshaw, et al's studies [21], which aimed to evaluate the relationship between the proportion of type I and type II muscle fibres and the parameters of the EMG signal such as MF and amplitude (RMS) in the vastus lateralis muscle. This research demonstrated that there were positive correlations between the value of MF and the proportion of type I muscle fibres as well as positive correlations between the value of RMS and the proportion of type II muscle fibres.…”
Section: Introductionmentioning
confidence: 77%
“…Those parameters are described as global parameters and their values change over time due to the fatigue processes within the muscle [10,11]. However, changes in the distribution of frequencies of the EMG power spectrum are also affected by changes in force level [12,13,14,15], recruitment of new, not fatigued, motor units [16,17,18,19,20], the proportion of muscle fibres [21], muscle type [22] and muscle length [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation